Student Perceptions of the Effectiveness of the Scola Learning Management System (LMS) in Improving the Quality of Learning - Beatrix Tanjung, Winnei Ray; Rugaiyah, Rugaiyah (Riviera Publishing, 2023)
This study aims to explore students' perceptions of the Teaching and Learning Process (Kegiatan Belajar Mengajar - KBM) involving the use of Learning Management System (LMS), particularly Scola. The research method employed is qualitative, supported by a descriptive quantitative approach, combining observations, literature reviews, and questionnaires as data collection tools. The results of the study indicate a high interest among students in using LMS Scola to support the teaching and learning process. Students express satisfaction with the use of LMS Scola, considering it effective, efficient, user-friendly, and ensuring a high level of data privacy. These findings indicate that the utilization of technology, especially LMS, can have a positive impact on the learning process, motivate students, and create a more interactive learning environment. The implications of this research provide a crucial push to encourage the adoption of LMS, such as Scola, in various educational institutions. By leveraging this technology, it is anticipated that the learning process can become more efficient, effective, and supportive of overall educational development. This study serves as a robust foundation for enhancing the quality of education through the integration of technology in the Teaching and Learning Process (KBM).